Impact of Family Support System in the Academic Performance of Grade 3 Pupils at a Public Elementary School in Rizal, Philippines - Juguilon, Irene Dionio (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Family interaction establishes a foundation for learning at home. Parents are children’s first teachers and the chief designers of children’s daily curricula. Parents make decisions about what to communicate and how to communicate with their children on a daily basis. Parental involvement has been defined and measured in multiple ways, including activities that parents participate in at home and at school, as well as positive attitudes that parents have toward their child's education. This study determined the impact of family support system in the mathematical performance of Grade 3 pupils of a public elementary school in Rizal, Philippines. The descriptive research method was used in this study, and the instrument used to collect data from the participants was a survey questionnaire. Cross-sectional survey type was also applied. Various statistical methods such as frequency counts, percentages, weighted means, and T-test were used in the interpretation of data. Results revealed that there are varied effects in the academic performance of family support system. Learners who received quality family support performed better academically than those who received less. It is recommended that parents support their children's early education at home as well as active involvement and participation in school. Finally, it is suggested that the school come up with support activities for parents in order to increase parental involvement at school.